IMPLEMENTASI KOMUNIKASI PERUBAHAN PERILAKU PASCA PELATIHAN OLEH PETUGAS PROMOSI KESEHATAN DI PUSKESMAS - Sinta Javani (ARCHIVE OF COMMUNITY HEALTH, 2023)
A reliable human resource apparatus is a valuable investment for an organization. So that a need for training to increase knowledge and behavior to realize professional health workers. UPTD Bapelkesmas has conducted behavior change communication training for health promoters. The targets of this evaluation are 30 participants of behavior change communication training (KPP). Data collection techniques are primary data in the form of questionnaires and secondary data by observation of individuals, groups and communities in the work areas of the participating health centers. This evaluation will be analyzed quantitatively by transforming to the Kirkpatrick model and describing the study at each level. The results are at a level I reaction alumni attended KPP training with a motivation of 87.7%, level II learning as a form of self-learning efforts of trainees of 94%, for level III behavior training alumni have behavior that affects peers and work performance of the puskesmas of 69.7%, level IV results alumni have performance that contributes to real performance in their institution of 76%. Based on a combined assessment (triangulation) between peers and direct supervisors, there was an increase in alumni performance of 92.6%. The results of this evaluation can be studied further as best practices or innovations in the health development sector. Keywords: Behavior Change Communication, Health Promotion, Evaluation